A Study of Preferred Learning Time of Online Learner in Multimedia Microlearning in Higher Education Context - Leong, Kelvin; Sung, Anna; Au, Robin; Lee, Ching (Online Journal for TVET Practitioners, 2022)
This study aims to explore when would online learners prefer to interact with multimedia microlearningâ€ in higher education context. Although microlearning is an emerging topic, most of the previous studies were focus on reporting the application results of microlearning, only very few of previous works were specifically conducted on discussing when would online learners prefer to interact with multimedia microlearning.Total population sampling approach was adopted and questionnaire was used to collect primary data. In total, 77 participants attempted the survey, the response rate is 32.6%. The findings from this study indicate that more learners prefer to study during morning or afternoon time rather than evening or midnight time (H2) (p